2018
DOI: 10.1515/ijcre-2017-0133
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Parameters for Reactive Separation of Gallic Acid

Abstract: Reactive extraction of gallic acid (GA) from aqueous solution was studied using extractant TOA and Aliquat 336 in hexanol and a comparative analysis were made for optimum extractant-diluent system with two factor central composite design. The model equations were developed using 13 experimentations, each with TOA and Aliquat 336. TOA and Aliquat 336 gave antagonistic and synergistic effects respectively for extraction of GA. The optimum conditions were observed as CTOA= 8.6 %, CGA0= 2.9 g/L and CALQ= 33.2 %, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The precipitation reaction leading to the formation of CaOx is instantaneous and is not due to the electron beam given the constant electron dose rate, as previously demonstrated. 47,54 Fig. S1 † shows the results of the beamblank experiment, where after 300 s of beam-blanking a COT nanoparticle maintains its phase and size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precipitation reaction leading to the formation of CaOx is instantaneous and is not due to the electron beam given the constant electron dose rate, as previously demonstrated. 47,54 Fig. S1 † shows the results of the beamblank experiment, where after 300 s of beam-blanking a COT nanoparticle maintains its phase and size.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium and oxalate ions encapsulated in GLC in a supersaturated aqueous environment undergo an instantaneous precipitation reaction, leading to the nucleation of a COT crystal. 46,47,54 Ni 2+ , present in a solution at a doping concentration, form Ni-water complexes via interactions with water. This presents an opportunity for Ni-water complexes to interact with the surface of the COT crystal, for example, with water that is part of the crystal structure and is located on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…HGA was adsorbed onto Na-montmorillonite [14], and a coal-based activated carbon [15]. HGA was extracted by molecular imprinted polymers [16], ethanol [17], tributyl phosphate [18,19], trioctyl amine and aliquat 336 [20,21]. All of these separation methods have their advantages and disadvantages in terms of selectivity, simplicity, performance, and cost [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Athankar et al (2015) studied the reactive extraction of gallic acid with tri- n -caprylamine dissolved in hexanol . Rewatkar and group focused on physical and chemical extraction studies on gallic acid using various extractants (Aliquat 336, TBP, and TOA) in alcohols (hexanol and octanol) and also presented few optimization studies (RSM ,, and ANN). Pandey et al, have shown the effect of polarity of solvents (MIBK, octanol, kerosene, decane) and type of extractant (TOA, TBP) on the extraction of gallic acid .…”
Section: Introductionmentioning
confidence: 99%